From Discrete Gravity Survey Data to a High-resolution Gravity Field Representation in the Nordic-Baltic Region. Issue 6 (2nd November 2017) - Märdla, Silja; Ågren, Jonas; Strykowski, Gabriel; Oja, Tõnis; Ellmann, Artu; Forsberg, René; Bilker-Koivula, Mirjam; Omang, Ove; Paršeliūnas, Eimuntas; Liepinš, Ivars; Kaminskis, Jānis
ABSTRACT: The deduction of a regularly spaced gravity anomaly grid from scattered survey data is studied, addressing mainly two aspects: reduction of gravity to anomalies and subsequent interpolation by various methods. The problem is illustrated in a heterogeneous study area and contrasting test areas including mountains, low terrains, and a marine area. Provided with realistic error estimates, Least Squares Collocation interpolation of Residual Terrain Model anomalies yields the highest quality gravity grid. In most cases, the Bouguer reduction and other interpolation methods tested are equally viable. However, spline-based interpolation should be avoided in marine areas with trackwise survey data.